Low-change-rate slurry as well as preparation and application thereof
By using graphene oxides, carbon nanotubes and other materials in electronic slurries, combined with ultrafine silicon nitride and inorganic salts and other enhancers, a slurry with low change rate was prepared, which solved the problem of degradation in high-temperature and high-humidity environments, and achieved the dual improvement of stability and conductivity, and was suitable for the field of high-demand electronic packaging.
Patent Information
- Application Number
- CN202510227994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The current electronic paste has decreased conductivity and weakened adhesion in high-temperature and high humidity environments, resulting in insufficient reliability and life in high-power LED packaging, semiconductor packaging, photovoltaic packaging and other fields.
Through the innovative selection of toughening agents and environmental adaptability enhancers, a low-variability slurry is prepared, which consists of conductive fillers, binders, toughening agents and environmental adaptability enhancers. The conductive fillers are composed of graphene oxides, carbon nanotubes and nanooxides. The binder is an organic silicon composite binder, the toughening agent is an ultrafine silicon nitride or silicate, and the environmental adaptability enhancer is a composite compound of inorganic salts and metal oxides or silicon oxides.
It achieves low rate of change of the slurry, strong stability, suitable for high temperature and high humidity environments, maintains conductivity, adhesion and thermal stability, extends the service life of the device, and is suitable for high-power LED packaging, semiconductor packaging, photovoltaic packaging and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic pastes, and in particular relates to a low-change rate paste and a preparation and application thereof. Background Art
[0002] As electronic devices develop towards higher power and smaller size, the requirements for electronic paste are increasing. As an important material for connecting electronic components and substrates, the performance of electronic paste directly affects the conductivity, thermal stability, mechanical strength and long-term stability of the device. At present, most electronic pastes on the market are affected by changes in temperature, humidity and external environment during use, resulting in problems such as decreased conductivity and weakened adhesion. Especially in high temperature and high humidity environments, the reliability and life of traditional pastes in packaging are often not enough to meet the needs of long-term applications.
[0003] Especially in the fields of high-power LED packaging, semiconductor packaging, photovoltaic packaging, and automotive electronic packaging, electronic paste needs to cope with long-term high temperature, high humidity and other harsh environments, and its conductivity, adhesion, thermal stability and resistance to environmental changes are particularly important. Therefore, it is urgent to develop an electronic paste with low change rate, strong stability, and suitable for high temperature and high humidity environments. Summary of the invention
[0004] The present invention aims to provide a slurry with low change rate, strong stability and suitable for high temperature and high humidity environment through innovative selection of toughening agent and environmental adaptability enhancer.
[0005] To achieve the above-mentioned purpose, the technical solution provided by the present invention is: a low-change rate slurry, which is composed of the following components, by mass: 20 to 50 parts of conductive filler, 10 to 20 parts of binder, 2 to 5 parts of toughening agent and 3 to 5 parts of environmental adaptability enhancer; the conductive filler is composed of 5 to 15 parts of graphene oxide, 10 to 20 parts of carbon nanotubes and 5 to 15 parts of nano oxide, the binder is an organic silicon composite binder, and the toughening agent is ultrafine silicon nitride or silicate.
[0006] In the above-mentioned low-change rate slurry, the nano-oxide is one or a combination of aluminum oxide, zinc oxide, silicon oxide, and titanium oxide; the environmental adaptability enhancer is a composite compound of an inorganic salt and a metal oxide or silicon oxide, the inorganic salt is one or a combination of calcium chloride, magnesium chloride, and sodium chloride, and the metal oxide is one of aluminum oxide and zinc oxide.
[0007] In the above-mentioned low-change rate slurry, the mass ratio of the inorganic salt to the metal oxide or silicon oxide is 1:5~2:1.
[0008] The present invention also provides a method for preparing the above-mentioned low-change rate slurry, comprising: mixing a conductive filler and a solvent, and performing ultrasonic dispersion treatment to uniformly disperse the conductive filler; Mixing the binder and the toughening agent, stirring evenly, to obtain a binder mixed solution; mixing the conductive filler solution with the binder mixed solution to obtain a slurry; Add environmental adaptability enhancer and continue stirring; Remove air bubbles from the slurry through vacuum degassing; The slurry is thermally cured or UV-cured to obtain a low-change rate slurry.
[0009] In the above-mentioned method for preparing the low-change rate slurry, the solvent is isophorone or dimethyl sulfoxide, and the mass ratio of the solvent to the conductive filler is 1:1 to 3:1.
[0010] In the preparation method of the low-change rate slurry, the curing temperature of the thermal curing is 100° C. to 150° C., and the curing time is 30 minutes to 2 hours.
[0011] In the above-mentioned method for preparing the low-change rate slurry, the curing time of ultraviolet curing is 5 minutes to 10 minutes.
[0012] Finally, the present invention also provides application of the low-change rate slurry in packaging.
[0013] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: (1) The conductive filler of the present invention has higher conductivity and mechanical stability: The combination of graphene oxide and carbon nanotubes of the present invention can form a "conductive network" at the filler level, which can enhance the conductive path by connecting with each other. The high specific surface area and strong π-π stacking effect of graphene oxide enable it to form an electron conduction channel with carbon nanotubes through van der Waals force and π-π interaction. Graphene oxide provides a large current distribution area, while carbon nanotubes enhance electron conduction through their long and continuous conductive channels. When the two are combined, graphene oxide can effectively reduce the agglomeration of carbon nanotubes and improve their dispersion, thereby optimizing the overall conductivity.
[0014] In terms of mechanical stability, carbon nanotubes provide strong mechanical reinforcement, while graphene oxide forms a network through its two-dimensional structure, which enhances the interfacial bonding between fillers. The combination of the two not only enhances the conductivity of the slurry, but also improves its mechanical stability.
[0015] (2) The binder and toughening agent of the present invention have an excellent synergistic effect, which effectively improves the overall structural stability of the slurry: the chemical structure of the organosilicon composite binder contains silicon-oxygen bonds, which give it excellent heat resistance, oxidation resistance and bonding properties. There are active sites on the surface of silicon nitride particles, which can interact with the silicon-oxygen bonds in the organosilicon binder to form crosslinks, thereby improving the dispersibility and bonding of the toughening agent in the slurry. This process can improve the adhesion between the toughening agent and the matrix, prevent the toughening agent particles from falling off or moving under the action of external forces, and the toughening agent particles can transfer stress through their internal bridging effect under stress, reduce stress concentration, and thus reduce the crack propagation of the material.
[0016] (3) The environmental adaptability enhancer of the present invention can effectively improve the adaptability of the slurry to the environment: the hygroscopic effect of the inorganic salt combined with the anti-hydrolysis characteristics of the metal oxide or silicon oxide can form an effective moisture barrier. The inorganic salt absorbs moisture in the air and forms a stable hydrate, thereby alleviating the impact of moisture on the slurry; at the same time, the metal oxide or silicon oxide effectively prevents the chemical reaction between moisture and organic components through its chemical inertness and surface adsorption, thereby enhancing the anti-hydrolysis and stability of the slurry. In addition, the inorganic salt can help reduce the thermal stress in the slurry by absorbing moisture and slowly releasing moisture at high temperature, thereby avoiding cracks or delamination caused by temperature changes. The strong thermal stability of the metal oxide or silicon oxide can provide the slurry with higher heat resistance and maintain the structural integrity under high temperature conditions. The two work synergistically to enhance the thermal stability and crack resistance of the slurry under temperature fluctuations and high temperature conditions.
[0017] (4) The slurry provided by the present invention has strong environmental adaptability, can resist moisture, temperature changes and oxidation, and ensure long-term stable operation; it has excellent mechanical properties, and improves crack resistance, impact resistance and pressure resistance; it has long-lasting electrical conductivity, and maintains high-efficiency electrical conductivity in harsh environments; it has outstanding thermal stability, is suitable for high-temperature working environments, and effectively avoids thermal cracks; it has a wide range of applications, and the low-change rate slurry of the present invention is suitable for the packaging field, especially high-power LED packaging, semiconductor packaging, photovoltaic packaging and automotive electronic packaging. The excellent performance of the slurry ensures that it can operate stably for a long time in these high-demand fields, meeting the requirements of modern electronic equipment for high reliability and high performance. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials can be purchased on the market unless otherwise specified. The % in the following embodiments, unless otherwise specified, are all mass percentages. The ratios in the following embodiments, unless otherwise specified, are all mass ratios.
[0019] First, a low-change rate slurry and a preparation method thereof provided by the present invention are described through Examples 1 to 3.
[0020] Example 1 A low-change rate slurry provided in this embodiment is composed of the following components, measured by mass: 20 parts of conductive filler, 10 parts of binder, 2 parts of toughening agent and 3 parts of environmental adaptability enhancer; the conductive filler is composed of 5 parts of graphene oxide, 10 parts of carbon nanotubes and 5 parts of nano oxide, the binder is an organic silicon composite binder, and the toughening agent is ultrafine silicon nitride; wherein the nano oxide is aluminum oxide, the environmental adaptability enhancer is a composite compound of an inorganic salt and a metal oxide, the inorganic salt is calcium chloride, the metal oxide is aluminum oxide, and the mass ratio of the inorganic salt to the metal oxide is 1:5.
[0021] This embodiment also provides a method for preparing the above-mentioned low-change rate material, comprising mixing a conductive filler and isophorone at a mass ratio of 1:1, and uniformly dispersing the conductive filler through ultrasonic dispersion treatment; Mixing the binder and the toughening agent, stirring evenly, to obtain a binder mixed solution; Mixing the conductive filler with a binder mixed solution to obtain a slurry; Add environmental adaptability enhancer and continue stirring; Remove air bubbles from the slurry through vacuum degassing; The slurry is thermally cured to obtain a low-change rate slurry.
[0022] The curing temperature of the thermal curing is 100° C. and the curing time is 1 hour.
[0023] Example 2 A low-change rate slurry provided in this embodiment is composed of the following components, measured by mass: 35 parts of conductive filler, 15 parts of binder, 4 parts of toughening agent and 4 parts of environmental adaptability enhancer; the conductive filler is composed of 10 parts of graphene oxide, 15 parts of carbon nanotubes and 10 parts of nano oxide, the binder is an organic silicon composite binder, and the toughening agent is a silicate; wherein the nano oxide is titanium oxide and the environmental adaptability enhancer is a composite compound of an inorganic salt and silicon oxide, the inorganic salt is magnesium chloride and sodium chloride, and the mass ratio of the inorganic salt to the silicon oxide is 1:1.
[0024] This embodiment also provides a method for preparing the above-mentioned low-change rate material, comprising mixing a conductive filler and dimethyl sulfoxide at a mass ratio of 2:1, and performing ultrasonic dispersion treatment to uniformly disperse the conductive filler; Mixing the binder and the toughening agent, stirring evenly, to obtain a binder mixed solution; Mixing the conductive filler with a binder mixed solution to obtain a slurry; Add environmental adaptability enhancer and continue stirring; Remove air bubbles from the slurry through vacuum degassing; The slurry is cured by ultraviolet light to obtain a low-change rate slurry.
[0025] The curing time of the ultraviolet curing is 10 minutes.
[0026] Example 3 A low-change rate slurry provided in this embodiment is composed of the following components, measured by mass: 50 parts of conductive filler, 20 parts of binder, 5 parts of toughening agent and 5 parts of environmental adaptability enhancer; the conductive filler is composed of 15 parts of graphene oxide, 20 parts of carbon nanotubes and 15 parts of nano oxide, the binder is an organic silicon composite binder, and the toughening agent is ultrafine silicon nitride; wherein the nano oxide is zinc oxide and silicon oxide; the environmental adaptability enhancer is a composite compound of an inorganic salt and a metal oxide, the inorganic salt is sodium chloride, the metal oxide is zinc oxide, and the mass ratio of the inorganic salt to the metal oxide is 2:1.
[0027] This embodiment also provides a method for preparing the above-mentioned low-change rate material, comprising mixing a conductive filler and dimethyl sulfoxide at a mass ratio of 3:1, and performing ultrasonic dispersion treatment to uniformly disperse the conductive filler; Mixing the binder and the toughening agent, stirring evenly, to obtain a binder mixed solution; Mixing the conductive filler with a binder mixed solution to obtain a slurry; Add environmental adaptability enhancer and continue stirring; Remove air bubbles from the slurry through vacuum degassing; The slurry is thermally cured to obtain a low-change rate slurry.
[0028] The curing temperature of the thermal curing is 150° C. and the curing time is 2 hours.
[0029] Examples 4 to 7 perform performance tests on a low-change rate slurry in Example 2 of the present invention, as detailed below.
[0030] Example 4 In this embodiment, a thermal stability test is performed on the low change rate slurry, including thermal expansion coefficient and thermal aging test.
[0031] Test method: The thermal expansion coefficient of the slurry was tested using a thermal expansion coefficient (CTE) tester, with the temperature range from room temperature to 200°C. The volume expansion of the slurry at different temperatures was measured.
[0032] The thermal aging test was carried out by placing the cured slurry samples in an oven for accelerated aging treatment at a high temperature of 150°C for 800 hours, and the conductivity changes of the slurry were checked regularly.
[0033] Test results: Coefficient of thermal expansion (CTE): The thermal expansion coefficient of this slurry is 3.2×10⁻ 6 / ℃, compared with common high conductive pastes, its thermal expansion coefficient is lower, indicating that it has better thermal stability in high temperature environment.
[0034] Thermal aging test: After 800 hours of accelerated aging at 150°C, the conductivity of the slurry did not change by more than 5%, showing a very low thermal aging effect, proving that the slurry has excellent thermal stability and low performance degradation. See Table 1 for specific data: Table 1
[0035] This performance indicates that the slurry is very suitable for long-term use in high-temperature environments, especially for use in high-power LED packaging, semiconductor packaging, photovoltaic packaging and other fields, where long-term high-temperature stability and conductive properties are key requirements.
[0036] Example 5 This example tests the resistivity of the low-change rate slurry: Test method: The resistivity of the slurry is measured using the four-probe method to ensure the accuracy of the test results. The resistivity of the slurry under different curing processes is compared to evaluate its conductive stability in high temperature environments.
[0037] Curing method: Thermal curing: curing temperature 100°C, curing time 1 hour.
[0038] UV curing: UV light source intensity is 1000 mJ / cm², curing time is 10 minutes.
[0039] The test results are shown in Table 2: Table 2
[0040] Resistivity after heat curing: After heat curing at 100℃ for 1 hour, the resistivity of the slurry was 0.05Ω·cm, showing a very low resistivity, and at 150℃ and 85% relative humidity, the resistivity increased by 5% and 6%, respectively, showing very good conductive stability. The increase in resistivity under high temperature environment is very small, indicating that the slurry can still maintain excellent conductivity in a long-term high temperature environment.
[0041] Resistivity after UV curing: The resistivity of the UV curing process after curing is 0.06Ω·cm, which is slightly higher than that of thermal curing. However, even under high temperature and high humidity conditions, the resistivity of the UV-cured slurry increased by 7% and 8% respectively, and it also maintained good conductivity. This shows that the UV-cured slurry also has good stability to a certain extent.
[0042] Example 6 This example tests the mechanical properties of the low-change rate slurry, including tensile strength and flexural strength.
[0043] Test method: Use a universal material testing machine to test the tensile strength and flexural strength of the cured slurry. The test sample is a cured low-change rate slurry, specifically a thin sheet sample of 50mm long and 10mm wide, and the test temperature is maintained at room temperature (25℃) and high temperature environment (100℃).
[0044] Test results: At room temperature, the tensile strength of the slurry is 30 MPa and the flexural strength is 65 MPa, indicating that the slurry has good mechanical properties.
[0045] Under high temperature of 100℃, the tensile strength of the slurry is maintained at 28MPa, and the bending strength is 60MPa, with a decrease of no more than 7%, showing very small strength changes. This shows that the mechanical properties of the slurry remain relatively stable under high temperature conditions, and it is suitable for high temperature working environments, especially in applications such as high-power LED packaging and semiconductor packaging that require long-term high temperature resistance, and it can still maintain strong structural stability.
[0046] Example 7 This embodiment is an environmental adaptability test of a low-change rate slurry, including moisture resistance and oxidation resistance tests.
[0047] Test method: Expose the slurry sample to a high humidity environment (85% relative humidity) and an acidic atmosphere to simulate the environmental changes under actual working conditions. Test the changes in adhesion in a humid environment and the changes in conductivity in an oxidizing environment.
[0048] Test results: Moisture resistance: After the slurry sample was exposed to 85% relative humidity for 200 hours, the conductivity decayed by only 2%, and the adhesion did not change significantly, showing good moisture resistance.
[0049] Oxidation resistance: After exposure to an acidic atmosphere for 500 hours, the conductivity and mechanical strength of the slurry showed almost no significant changes, showing excellent oxidation resistance.
[0050] The low-change rate slurry demonstrated in the above embodiments shows significant low-change characteristics in multiple key performance tests, especially in thermal stability, conductivity, mechanical strength and environmental adaptability under high temperature, high humidity and oxidative environments. Specifically, after aging at 150°C for 800 hours, the conductivity of the slurry does not change by more than 5%, showing an extremely low thermal aging effect; under different curing processes, the resistivity changes are also very small, and the conductivity in a high humidity environment is only attenuated by 2%. In addition, the tensile strength and flexural strength of the slurry at room temperature and 100°C also change by less than 7%, showing excellent mechanical stability. This series of tests shows that the low-change rate slurry can effectively maintain its conductivity, mechanical properties and environmental adaptability under long-term high temperature, high humidity and oxidative environments, greatly improving its reliability in long-term stable operation, and is particularly suitable for applications that require long-term high performance such as high-power LED packaging, semiconductor packaging and photovoltaic packaging.
[0051] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A low-change rate slurry, characterized in that: The invention is composed of the following components by mass: 20 to 50 parts of conductive filler, 10 to 20 parts of binder, 2 to 5 parts of toughening agent and 3 to 5 parts of environmental adaptability enhancer; the conductive filler is composed of 5 to 15 parts of graphene oxide, 10 to 20 parts of carbon nanotubes and 5 to 15 parts of nano oxide, the binder is an organic silicon composite binder, and the toughening agent is ultrafine silicon nitride or silicate.
2. A low change rate slurry according to claim 1, characterized in that: The nano-oxide is one or a combination of aluminum oxide, zinc oxide, silicon oxide, and titanium oxide; the environmental adaptability enhancer is a composite compound of an inorganic salt and a metal oxide or silicon oxide, the inorganic salt is one or a combination of calcium chloride, magnesium chloride, and sodium chloride, and the metal oxide is one of aluminum oxide and zinc oxide.
3. A low change rate slurry according to claim 2, characterized in that: The mass ratio of the inorganic salt to the metal oxide or silicon oxide is 1:5 to 2:
1.
4. The method for preparing a low-change rate slurry according to any one of claims 1 to 3, characterized in that: The following steps are involved: The conductive filler and the solvent are mixed and subjected to ultrasonic dispersion treatment to obtain a conductive filler solution; Mixing the binder and the toughening agent, stirring evenly, to obtain a binder mixed solution; mixing the conductive filler solution with the binder mixed solution to obtain a slurry; Add environmental adaptability enhancer and continue stirring; After stirring, vacuum degassing is performed; The slurry is thermally cured or UV-cured to obtain a low-change rate slurry.
5. The method for preparing a low-change rate slurry according to claim 4, characterized in that: The solvent is isophorone or dimethyl sulfoxide, and the mass ratio of the solvent to the conductive filler is 1:1 to 3:
1.
6. The method for preparing a low-change rate slurry according to claim 4, characterized in that: The curing temperature of the thermal curing is 100° C. to 150° C., and the curing time is 30 minutes to 2 hours.
7. The method for preparing a low-change rate slurry according to claim 4, characterized in that: The curing time of the ultraviolet curing is 5 minutes to 10 minutes.
8. Use of the low-change rate slurry according to any one of claims 1 to 3 in packaging.
Citation Information
Patent Citations
Weak electrical contact composite electrically conductive material, and production method thereof
CN107098689A
Conductive epoxy resin and preparation method thereof
CN110343368A
Composite carbon nanotube conductive slurry and preparation process thereof
CN111640526A
Composite conductive particle, polyphenyl ether compound and preparation method thereof
CN118231023A
High-toughness and high-conductivity epoxy resin composition as well as preparation method and application thereof
CN119192774A
Cited By
High-durability organic silicon conductive adhesive and preparation method thereof
CN119955467A